Effect of Molecular Weight and Carboxylic Density of Polycarboxylates Ether Superplasticizer on Its performance in Cement Pastes - Alya HARICHANE; Abdelbaki BENMOUNAH; Johann PLANK (Journal of Materials and Engineering Structures, 2023)
The main difficulty encountered in the formulation of high performance concrete (HPC) consists in choosing the most efficient cement-superplasticizer pair allowing to obtain maximum water reduction, good workability of the concrete in the fresh state and very good mechanical resistance in the hardened state. The aim of this work is to test the efficient of three polycarboxylate ether based superplasticizers (PCE) marketed in Algeria with CEMI 52.5 R cement and to study the effect of chemical structure of PCE on zeta potential, rheological and mechanical properties of cement pastes. The property of the polymers in cement was tested by a Malvern Zetasizer 2000 apparatus and VT 550 viscometer. Results showed that the zeta potential and its rheological properties are related with the molecular weight and the carboxylic density of PCE. The PCE with a moderate molecular weight and highest carboxylic groups had the best dispersion (high value of zeta potential) and lowest viscosity. The effect of chemical structure of PCEs on mechanical properties are evaluated by formulation of cement mortar with this PCEs, the result shows that there are a correlation between zeta potential of polymer and compressive strength of cement paste.